High-hardness high-wear-resistance low-smoke halogen-free sheath material as well as preparation method and application thereof

By using resin systems such as high-density polyethylene resins, combined with components such as fine-grained aluminum hydroxide and antioxidants, the problem of insufficient hardness and wear resistance of existing low-smoke halogen-free material resins is solved, and high-quality preparation The hardness and wear-resistant low-smoke and halogen-free sheath material meets the strict performance requirements of optical cables and improves the overall performance of optical cables.

CN119144077APending Publication Date: 2024-12-17SUZHOU HENGLI COMM MATERIAL
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411227547.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

When existing low-smoke halogen-free resin is used in optical cable sheath, the surface hardness is insufficient and the wear resistance is poor, and it cannot pass strict wear resistance tests, which cannot meet the needs of overhead optical cables in harsh environments, and traditional cable types exist. Some defects affect the construction effect of fiber optic cables.

Method used

Resin system using high-density polyethylene resin, metallocene catalyzed linear low-density polyethylene, bimodal polyethylene, maleic anhydride grafted polyethylene, fine-grain aluminum hydroxide, antioxidants and silicon-based lubricants, combined with 50 % carbon black content, high hardness, wear-resistant low-smoke, halogen-free sheath material is prepared through twin-screw extrusion processing and single-screw granulation technology.

Benefits of technology

It significantly improves the hardness and wear resistance of the sheath material, meets the high hardness and mechanical performance requirements of the optical cable, extends the service cycle, and improves the overall performance of the optical cable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005025090540000021
    Figure BDA0005025090540000021
  • Figure BDA0005025090540000051
    Figure BDA0005025090540000051
  • Figure BDA0005025090540000061
    Figure BDA0005025090540000061
Patent Text Reader

Abstract

The invention relates to a high-hardness wear-resistant low-smoke halogen-free sheath material as well as a preparation method and application thereof, and belongs to the technical field of cable sheath materials. The high-hardness wear-resistant low-smoke halogen-free sheath material provided by the invention comprises the following components in parts by mass: 12-18 parts of high-density polyethylene resin; 20 to 25 parts of metallocene catalyzed linear low density polyethylene; 4-8 parts of bimodal polyethylene; 7 to 10 parts of maleic anhydride grafted polyethylene; 75-90 parts of aluminum hydroxide with a fine particle size; 0.5 to 1 part of an antioxidant; 1-1.5 parts of a silicon lubricant; and 1-2 parts of black masterbatch. The low-smoke halogen-free sheath material prepared by the invention can simultaneously obtain better processability, hardness and wear resistance, and the performance of the low-smoke halogen-free sheath material is superior to that of a traditional material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cable sheath materials, in particular to a high-hardness, wear-resistant, low-smoke, halogen-free sheath material and a preparation method and application thereof. Background Art

[0002] The traditional low-smoke halogen-free material resin on the market is composed of vinyl acetate copolymer and polyethylene resin, combined with flame retardant inorganic alkali metal hydroxide. After this type of low-smoke halogen-free material is made into an optical cable sheath, the surface hardness is insufficient and the wear resistance is poor. It cannot pass the wear test of 3.0mm outer diameter optical cable with a wall thickness of 0.7mm (reservation requires ≥0.5mm). Referring to the ISO 6722 standard, the test is stricter than the standard: load 7N, 2500 times (grinding back and forth 2500 times), 0.45mm diameter steel needle, the sample is worn for a length range of 50mm, and the frequency is 50 to 70 times per minute.

[0003] The laying environment of overhead optical cables is relatively harsh, and they are prone to certain friction with external substances. Ordinary low-smoke halogen-free materials cannot guarantee the integrity of the optical cables during their service life.

[0004] Digital divide: The contradiction between the current low-speed network and the high-speed network for online office work is becoming increasingly prominent. Traditional cable types have some defects, which makes the effect of optical fiber cable construction unsatisfactory. It is necessary to develop a reinforced lightweight access cable that can be used for subsequent home access.

[0005] Performance factors: Compared with existing optical cables, customers have more stringent performance requirements for optical cables, including the wear resistance and tensile performance of the outer sheath: the standard thickness of the optical cable wall is only 0.7mm, requiring the use of a 0.45mm fine steel needle, a force of 7N, and 2500 times of grinding back and forth. By continuously trying sheath materials of different hardness, the wear resistance of the optical cable is improved. When the hardware is stretched, the tight sleeve material with low hardness has an impact on the stretching of the hardware. It is necessary to increase the hardness of the tight sleeve at the same time to ensure the tensile performance of the optical cable hardware. However, the existing solution cannot meet this requirement.

[0006] In summary, there is an urgent need to develop a high-hardness, wear-resistant, low-smoke, halogen-free sheath material for optical cables. Summary of the invention

[0007] In order to solve the above technical problems, the present invention provides a high-hardness, wear-resistant, low-smoke, halogen-free sheath material and its preparation method and application. The present invention abandons the traditional vinyl acetate copolymer, and adds a resin system of high-density polyethylene resin, metallocene-catalyzed linear low-density polyethylene, bimodal polyethylene and maleic anhydride grafted polyethylene that meet the requirements of high-speed extrusion during the debugging process; a flame retardant of fine-particle aluminum hydroxide, a black masterbatch with 50% carbon black content, a silicon-based lubricant and an AT-10 antioxidant. The above resin system and flame retardant can simultaneously obtain better processing performance, hardness and wear resistance.

[0008] The present invention is achieved through the following technical solutions:

[0009] The first object of the present invention is to provide a high-hardness, wear-resistant, low-smoke, halogen-free sheath material, which comprises the following components by weight:

[0010]

[0011] In one embodiment of the present invention, the high-density polyethylene resin is Borealis 3364 resin, Qilu Petrochemical QHJ02, Dow Chemical 3364 resin and other processing-grade high-density polyethylene resins.

[0012] In one embodiment of the present invention, the tensile strength of the bimodal polyethylene is ≥40 MPa, and the elongation at break is ≥600%.

[0013] In one embodiment of the present invention, the particle size value D97 of the fine-particle aluminum hydroxide is ≤6.0 μm.

[0014] In one embodiment of the present invention, the silicon-based lubricant is a silicone masterbatch with a content of more than 50%, and the carrier is a polyethylene carrier.

[0015] In one embodiment of the present invention, the melt index of the metallocene-catalyzed linear low-density polyethylene at 190° C. and a load of 2.16 kg should be ≤6.0 g / 10 min.

[0016] The metallocene-catalyzed linear low-density polyethylene is a linear low-density polyethylene produced by using metallocene as a catalyst.

[0017] In one embodiment of the present invention, the grafting rate of the maleic anhydride grafted polyethylene is ≥30%.

[0018] In one embodiment of the present invention, the antioxidant is selected from one or more of AT-10 antioxidant, antioxidant 1010, antioxidant 168, antioxidant 300, antioxidant DLTP, antioxidant 1076 and antioxidant RD.

[0019] In one embodiment of the present invention, the carbon black content of the black masterbatch is 45% to 55%, and the carrier is a polyethylene carrier.

[0020] In one embodiment of the present invention, the hardness of the low-smoke halogen-free sheath material is ≥60.

[0021] The second object of the present invention is to provide a method for preparing the high-hardness, wear-resistant, low-smoke, halogen-free sheath material, comprising the following steps:

[0022] (1) adding the high-density polyethylene resin, metallocene-catalyzed linear low-density polyethylene, bimodal polyethylene, maleic anhydride-grafted polyethylene, fine-particle aluminum hydroxide, antioxidant, silicon-based lubricant and black masterbatch according to weight parts into an internal mixer for mixing and plasticizing;

[0023] (2) The mixed material obtained in step (1) is subjected to twin-screw extrusion processing, and then subjected to single-screw extrusion granulation to obtain the high-hardness, wear-resistant, low-smoke, halogen-free sheath material.

[0024] In one embodiment of the present invention, in step (1), the plasticizing temperature is 140° C. to 185° C., and the plasticizing time is ≥15 min.

[0025] The third object of the present invention is to provide the use of the high-hardness, wear-resistant, low-smoke, halogen-free sheath material in the preparation of optical cables.

[0026] The functions of the components in the high-hardness, wear-resistant, low-smoke, halogen-free sheath material of the present invention are as follows: the function of high-density polyethylene resin is to improve wear resistance; the metallocene-catalyzed linear low-density polyethylene improves strength and elongation at break performance; the function of bimodal polyethylene is to improve processing performance; the maleic anhydride grafted polyethylene is combined with the inorganic powder through the resin to ensure strength and elongation at break performance; the fine particle size of fine-particle aluminum hydroxide ensures wear resistance and aluminum hydroxide ensures flame retardancy; the function of the antioxidant is to reduce the aging time of the plastic and increase the service life; the silicon-based lubricant improves the flow performance of the material processing process and ensures a smooth cable surface during the processing process; the function of the black masterbatch is coloring.

[0027] The above technical solution of the present invention has the following advantages compared with the prior art:

[0028] The present invention provides a high-hardness, wear-resistant, low-smoke, halogen-free sheath material and a preparation method and application thereof. The hardness and wear resistance of the prepared product are superior to those of traditional materials.

[0029] (1) The high-density polyethylene resin for high-speed extrusion is Borealis 3364 high-density polyethylene resin, which has high hardness and belongs to the extrusion grade. The hardness of the material and the surface smoothness of the processing are significantly improved;

[0030] (2) Fine-particle aluminum hydroxide is aluminum hydroxide with a particle size value D97≤6.0μm. The powder is more evenly dispersed in the resin, the microscopic molecules are smoother, the friction force is reduced in the wear resistance test, and it is significantly improved in the sheath material wear resistance test;

[0031] (3) Silicone lubricant is a silicone masterbatch with a content of more than 50%, which reduces the friction between the die mouth and the optical cable during optical cable extrusion and improves the surface smoothness;

[0032] (4) The product of the present invention has high hardness and high wear resistance, and also has excellent mechanical properties to meet the needs of the use and laying of optical cables. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical scheme and advantages of the present invention clearer, the technical scheme in the embodiment of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. The process parameters of the following embodiments that do not specify specific conditions are usually based on conventional conditions.

[0034] The endpoints and any values ​​of the ranges disclosed in the present invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in the present invention.

[0035] The present invention will be further described in detail below with reference to specific embodiments and comparative examples.

[0036] If the specific techniques and reaction conditions are not specified in the examples of the present invention, the techniques or conditions described in the literature in the field or the product instructions can be used. Any reagents, instruments or equipment without manufacturer specified can be obtained from the market.

[0037] Among them, the high-density polyethylene resin for high-speed extrusion was purchased from Borealis HE3364 resin;

[0038] Metallocene-catalyzed linear low-density polyethylene was purchased from Dow Chemical, 4404G;

[0039] Bimodal polyethylene was purchased from Borealis, FB2230;

[0040] Maleic anhydride grafted polyethylene was purchased from Ningbo Nengzhiguang, MC226;

[0041] Fine-particle aluminum hydroxide was purchased from Luoyang Zhongchao, AH-101;

[0042] Aluminum hydroxide with conventional particle size was purchased from Zhongzhou Aluminum Hydroxide;

[0043] AT-10 antioxidant was purchased from Shanghai Dirui, AT-10;

[0044] Silicone lubricant was purchased from Jiahua, GT-150P;

[0045] The black masterbatch with 50% carbon black content was purchased from Nantong Qixin, MH200A.

[0046] Example 1

[0047] This embodiment provides a high-hardness, wear-resistant, low-smoke, halogen-free sheath material and a preparation method thereof. The names and weight proportions of the components are as follows:

[0048]

[0049] Among them, the high-density polyethylene resin for high-speed extrusion is Borealis' 3364 resin;

[0050] The tensile strength of bimodal polyethylene is ≥40Mpa, and the elongation at break is ≥600%;

[0051] Fine-particle aluminum hydroxide is aluminum hydroxide with a particle size value D97≤6.0μm;

[0052] The silicone-based lubricant is a silicone masterbatch with a content of 50% or more.

[0053] The raw materials of each component are selected according to the ratio, the components accurately weighed are mixed and plasticized by an internal mixer, processed by twin-screw extrusion, and then granulated by single-screw extrusion, and the finished products are air-cooled, conveyed and packaged.

[0054] The preparation method comprises the following steps:

[0055] (1) The raw material components, calculated by weight, including 15 parts of high-speed extruded high-density polyethylene resin, 22 parts of metallocene-catalyzed linear low-density polyethylene, 5 parts of bimodal polyethylene, 9 parts of maleic anhydride grafted polyethylene, 85 parts of fine-particle aluminum hydroxide, 0.5 parts of AT-10 antioxidant, 1.5 parts of silicone lubricant, and 2 parts of black masterbatch with 50% carbon black content, were added to an internal mixer for mixing and plasticizing at a plasticizing temperature of 180° C. for 15 min, so that the materials were fully mixed and formed into agglomerates.

[0056] (2) The obtained mixed material is subjected to twin-screw extrusion, wherein the twin-screw extruder includes 8 temperature sections, and the temperature sections of the twin-screw extruder are 80°C, 90°C, 100°C, 110°C, 120°C, 110°C, 100°C, and 100°C, respectively, and the upper screw speed of the twin-screw extruder is 200 rpm. Then, the mixed material is subjected to single-screw extrusion granulation, and the temperatures of the single-screw feed section, melting section, and die head are 80°C, 100°C, and 150°C, respectively. After extrusion, the finished product is air-cooled, transported, and packaged.

[0057] Comparative Example 1

[0058] This comparative example provides a sheath material and a preparation method thereof, which is similar to Example 1, except that the fine-particle aluminum hydroxide is replaced with a conventional-particle aluminum hydroxide (D97 is about 11 μm). The details are as follows:

[0059] The names and weight proportions of each component are as follows:

[0060]

[0061] Among them, the high-density polyethylene resin for high-speed extrusion is Borealis' 3364 resin;

[0062] The tensile strength of bimodal polyethylene is ≥40Mpa, and the elongation at break is ≥600%;

[0063] Conventional particle size aluminum hydroxide is aluminum hydroxide with a particle size value D97 of about 11 μm;

[0064] The silicone-based lubricant is a silicone masterbatch with a content of 50% or more.

[0065] The preparation method of the sheath material in this comparative example is the same as that in Example 1.

[0066] Comparative Example 2

[0067] This comparative example provides a sheath material and a preparation method thereof, which is similar to Example 1, except that: the high-density polyethylene resin for high-speed extrusion is 25 parts; the metallocene-catalyzed linear low-density polyethylene is 12 parts. The details are as follows:

[0068] The names and weight proportions of each component are as follows:

[0069]

[0070] Among them, the high-density polyethylene resin for high-speed extrusion is Borealis' 3364 resin;

[0071] The tensile strength of bimodal polyethylene is ≥40Mpa, and the elongation at break is ≥600%;

[0072] Fine-particle aluminum hydroxide is aluminum hydroxide with a particle size value D97≤6.0μm;

[0073] The silicone-based lubricant is a silicone masterbatch with a content of 50% or more.

[0074] The preparation method of the sheath material in this comparative example is the same as that in Example 1.

[0075] Comparative Example 3

[0076] This comparative example provides a sheath material and a preparation method thereof, which is similar to Example 1, except that: the number of parts of metallocene-catalyzed linear low-density polyethylene is 27 parts; and no bimodal polyethylene is added. The details are as follows:

[0077] The names and weight proportions of each component are as follows:

[0078]

[0079]

[0080] Among them, the high-density polyethylene resin for high-speed extrusion is Borealis' 3364 resin;

[0081] Fine-particle aluminum hydroxide is aluminum hydroxide with a particle size value D97≤6.0μm;

[0082] The silicone-based lubricant is a silicone masterbatch with a content of 50% or more.

[0083] The preparation method of the sheath material in this comparative example is the same as that in Example 1.

[0084] Comparative Example 4

[0085] This comparative example provides a sheath material and a preparation method thereof, which is similar to Example 1, except that: the metallocene-catalyzed linear low-density polyethylene is 25 parts; the maleic anhydride-grafted polyethylene is 6 parts. The details are as follows:

[0086] The names and weight proportions of each component are as follows:

[0087]

[0088] Among them, the high-density polyethylene resin for high-speed extrusion is Borealis' 3364 resin;

[0089] The tensile strength of bimodal polyethylene is ≥40Mpa, and the elongation at break is ≥600%;

[0090] Fine-particle aluminum hydroxide is aluminum hydroxide with a particle size value D97≤6.0μm;

[0091] The silicone-based lubricant is a silicone masterbatch with a content of 50% or more.

[0092] The preparation method of the sheath material in this comparative example is the same as that in Example 1.

[0093] Comparative Example 5

[0094] This comparative example provides a sheath material and a preparation method thereof, which is similar to Example 1, except that the high-density polyethylene resin is Zhenhai Refining and Chemical Co., Ltd. high-density polyethylene 6098. The details are as follows:

[0095] The names and weight proportions of each component are as follows:

[0096]

[0097] Among them, the high-density polyethylene resin extruded at high speed is Zhenhai Refining and Chemical High-density Polyethylene 6098;

[0098] The tensile strength of bimodal polyethylene is ≥40Mpa, and the elongation at break is ≥600%;

[0099] Fine-particle aluminum hydroxide is aluminum hydroxide with a particle size value D97≤6.0μm;

[0100] The silicone-based lubricant is a silicone masterbatch with a content of 50% or more.

[0101] The preparation method of the sheath material in this comparative example is the same as that in Example 1.

[0102] Performance Test:

[0103] (1) Density: refer to GB / T 1033.1-2008;

[0104] (2) Elongation at break: refer to GB / T 1040.3-2006;

[0105] (3) Limiting oxygen index: refer to GBT 2406.2-2009;

[0106] (4) Wear resistance: refer to ISO 6722;

[0107] (5) Hardness performance: refer to GB / T 2411-2008.

[0108] The performance test results of the high-hardness, wear-resistant, low-smoke, halogen-free sheath materials prepared in Example 1 of the present invention and Comparative Examples 1 to 5 are shown in Table 1:

[0109] Table 1 Performance test results of high hardness and wear-resistant low-smoke halogen-free sheath materials in the examples and comparative examples

[0110]

[0111] As can be seen from Table 1, the difference between Comparative Example 1 and Example 1 is that the fine-particle aluminum hydroxide is replaced with conventional-particle aluminum hydroxide (D97 is about 11 μm). It can be seen from the performance test results in Table 1 that the wear resistance of the finished product prepared by the conventional-particle aluminum hydroxide of the product prepared in Comparative Example 1 is unqualified. It can be seen that conventional-particle aluminum hydroxide cannot meet the requirements of the present invention.

[0112] The difference between Comparative Example 2 and Example 1 is that the high-density polyethylene resin extruded at high speed is 25 parts; the metallocene-catalyzed linear low-density polyethylene is 12 parts. It can be seen from the performance test results in Table 1 that the elongation at break of the product prepared in Comparative Example 2 is unqualified. This is because too little addition of the metallocene-catalyzed linear low-density polyethylene will affect the elongation performance of the finished particles.

[0113] The difference between Comparative Example 3 and Example 1 is that the number of parts of metallocene-catalyzed linear low-density polyethylene is 27 parts; no bimodal polyethylene is added. It can be seen from the performance test results in Table 1 that the wear resistance of the product prepared in Comparative Example 3 is unqualified. Although the metallocene-catalyzed linear low-density polyethylene can meet the elongation performance of the finished product test, due to the lack of bimodal polyethylene, the overall hardness of the material affects the wear resistance.

[0114] The difference between Comparative Example 4 and Example 1 is that the metallocene-catalyzed linear low-density polyethylene is 25 parts and the maleic anhydride-grafted polyethylene is 6 parts. It can be seen from the performance test results in Table 1 that the elongation at break of the product prepared in Comparative Example 4 is unqualified. The amount of maleic anhydride-grafted polyethylene is too small, resulting in unqualified mechanical properties of the material, such as strength and elongation at break.

[0115] The difference between Comparative Example 5 and Example 1 is that the high-density polyethylene resin is Zhenhai Refining and Chemical High-density Polyethylene 6098. From the performance test results in Table 1, it can be seen that the optical cable sheath of Comparative Example 5 is rough due to the extrusion, and it is impossible to prepare samples for testing the wear resistance.

[0116] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. A high-hardness, wear-resistant, low-smoke, halogen-free sheath material, characterized in that: Calculated by mass, it includes the following components:

2. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The high-density polyethylene resin is one or more of Borealis 3364 resin, Qilu Petrochemical QHJ02 and Dow Chemical 3364 resin.

3. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The bimodal polyethylene has a tensile strength of ≥40 MPa and an elongation at break of ≥600%.

4. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The particle size value D97 of the fine-particle aluminum hydroxide is ≤6.0 μm.

5. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The silicon-based lubricant is a polyethylene carrier silicone masterbatch with a content of more than 50%.

6. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The melt index of the metallocene-catalyzed linear low-density polyethylene at 190° C. and a load of 2.16 kg should be ≤6.0 g / 10 min.

7. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The grafting rate of the maleic anhydride grafted polyethylene is ≥30%.

8. The high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to claim 1, characterized in that: The antioxidant is selected from one or more of AT-10 antioxidant, antioxidant 1010, antioxidant 168, antioxidant 300, antioxidant DLTP, antioxidant 1076 and antioxidant RD; And / or, the carbon black content of the black masterbatch is 45% to 55%, and the carrier is polyethylene.

9. A method for preparing the high-hardness, wear-resistant, low-smoke, halogen-free sheath material according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding the high-density polyethylene resin, metallocene-catalyzed linear low-density polyethylene, bimodal polyethylene, maleic anhydride-grafted polyethylene, fine-particle aluminum hydroxide, antioxidant, silicone lubricant and black masterbatch according to parts by mass into an internal mixer for mixing and plasticizing; (2) The mixture obtained in step (1) is subjected to twin-screw extrusion processing, and then granulated by single-screw extrusion to obtain the high-hardness, wear-resistant, low-smoke, halogen-free sheath material.

10. Use of the high-hardness, wear-resistant, low-smoke, halogen-free sheathing material according to any one of claims 1 to 8 in the preparation of optical cables.